The sustainable succession of family-owned businesses in the agriculture-farming sector in Egypt - Aboulmagd, Sara Khaled (AUC Knowledge Fountain, 2017)
Agriculture sustainability is considered a pillar for a country’s economic stability, and equally, Family Owned Businesses (FOBs) are considered a primary factor that contributes to the economic growth of a country, especially when 40% of the country’s GDP are considered FOBs. However, various studies have stated that a large percentage of Family Owned and Controlled Businesses (FOBs and FCBs) have not been successful with their generational transition process, thus affecting their sustainability. In addition, sources also stated that the agriculture sector in Egypt has been facing challenges throughout the past 60 years due to various factors, leading several FOBs in the agriculture farming business to face sustainable succession difficulties, which often results in the deterioration of the agricultural filed in the Egyptian economy. Hence, researching the area of sustainable succession of FOBs in the agriculture-farming sector in Egypt is a crucial area for research given the lack of available data on the mentioned subject and the lack of attention this sector is receiving. With reference to the definition of family business as “a business governed and/or managed on a sustainable, potentially cross-generational basis” (as cited in Smyrnios et al., 2013, p. 267), there are various factors that contribute to the success or failure of the succession of FOBs worldwide of which governance is positioned on the top of the factors list since there is an evident lack of good strategic management planning for succession and the know-how of its application. Therefore, this thesis aims to investigate the long-term continuity of FOBs in the agriculture-farming sector in Egypt while analyzing factors that contribute to their sustainable succession. The adopted research model in this thesis is Joseph Alex Maxwell’s Qualitative Research Design approach utilized to conduct the research and data analysis. The study examines the literature that investigated FOB succession; the nature and idiosyncratic culture of FOBs, the factors affecting family owned businesses succession, and the practices and procedures implemented for generational transitions, in an attempt to answer the research question of What are the factors that contribute to successful succession in agriculture-farming family owned businesses in Egypt, causing them to become sustainable? Six agriculture-farming FOBs case studies were investigated through in-depth semi-structured interviews, along with four interviews conducted with experts from the field to validate the acquired information from the cases, to help formulate an understanding of the succession factors taking place, and provide solutions and lessons learnt that would serve as insights to the generational transition and sustainable succession of FOBs in the agriculture-farming sector in newly reclaimed lands within the Egyptian economy. The data gathered from the field was analyzed through coding and then grouped into the identified categories from the literature and field study. The research has found that there are several factors contributing to the current succession practices within agriculture-farming fobs that fall under three primary identified criteria; 1) preparation level of successor; which includes the successors’ educational and technical background, trainings and external experience as well as the successors’ involvement in the business and upbringing (Nurturing and Apprenticeship), 2) Social and Cultural Norms: Successor’s gender and the planning, management and control activities, 3) Successor’s Individual Characteristics: personal traits and interests (passions) as well as the opportunity cost.